Ability or luck: A systematic review of interpersonal attributions of success - Hamilton, Odessa S.; Lordan, Grace (Frontiers in Psychology, 2023)
The role of luck in success has a relatively minor, albeit consistent history in academic discourse, with a striking lack of literature engaging with notions of luck within occupational environments. Elucidating why people attribute their own success to luck over ability has predominated in the literature, with interpersonal attributions receiving less attention. Here, we center on systematically summarizing the evidence on interpersonal attributions of success as a function of ability or luck, with a particular focus on whether these differs by gender and race. The perception of the success of others from different sociodemographic groups, and how it is attributed, is a crucial leverage point for inclusion and diversity. Particularly as women and ethnic groups continue to be systematically disadvantaged in the workforce. Ignoring the role of luck conceals and augments privilege, even if not deliberately or consciously invoked. Using the Prisma protocol, this review offers evidence from experiments, published between 1970 and 2020, derived from five electronic bibliographic databases; Business Source Complete; PsychINFO; Scopus; Web of Science; and Google Scholar. There were a limited number of studies on gender that found an effect, but with few exceptions, the papers that pertain to race converged on the understanding that interpersonal attributions of success were predicated on this immutable factor. Such that black individuals were more often viewed as lucky in their success and less able, which translates to lesser opportunity and reward. Decades of research have pointed to individuals making systematic attribution errors in success by gender and race; this review only partially substantiates this consensus and provides narrow support for the view that those believed to be the most talented in society may merely be the luckiest. We add to evidence that context matters.